Pollution Characteristics, Sources, and Health Risk Assessment of Heavy Metals in the Surface Soil of Lushan Scenic Area, Jiangxi Province, China - Zhang, Shunjie; Ye, Hui; Zhang, Aijuan; Ma, Yanyu; Liu, Qing; Shu, Qiang; Cao, Xilin (Frontiers in Environmental Science, 2022)
Heavy metal pollution at tourist attractions centers has caused widespread concern. In this study, the concentration of seven heavy metals (Pb, Cu, Cr, Zn, Ni, As, and Mn) in the surface soil of the Lushan scenic area was measured, and their pollution characteristics were assessed using the Nemerow comprehensive pollution index and geo-accumulation index; further, the human non-carcinogenic and carcinogenic risks were evaluated by the U.S. Environmental Protection Agency health risk assessment model. Correlation analysis, cluster analysis, and a positive matrix factorisation model were used to analyse the heavy metal sources. The results indicated that the heavy metal concentrations did not exceed the pollution threshold levels. The hazard quotients for the six heavy metals (Pb, Cu, Cr, Zn, Ni, and As) are below the threshold for non-carcinogenic health risk, whereas the carcinogenic health risk in the region is at an “acceptable” level; however, because of the high contribution of As, the carcinogenic health risks to residents of this area require continuous monitoring. Analysis revealed six sources of the pollutants: soil parent material, altitude, surface accumulation of organic matter, industrial dustfall, local human activities (life and agriculture), and tourism. These findings provide a scientific basis for developing appropriate strategies for a sustainable development of the scenic area.